2020
DOI: 10.1080/21645698.2020.1809318
|View full text |Cite
|
Sign up to set email alerts
|

Improvementofsugarcane for borer resistance usingAgrobacteriummediated transformation ofcry1Acgene

Abstract: The sugarcane (Saccharum X officinarum) is one of the most important crops used to produce sugar and raw material for biofuel in the world. One of the main causes for sucrose content and yield losses is the attack by insect. In this investigation, cry1Ac gene was introduced into sugarcane variety GT54-9 (C9) using the Agrobacterium tumefaciens transformation method for transgenic sugarcane production presenting insect-resistance. The A. tumefaciens strain GV1303 including pARTcry1Ac vector was used for the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In 1990, the first transgenic sugarcane was produced using the gun bombardment method (Bower & Birch, 1992). Arencibia et al (1998) later reported a novel sugarcane Agrobacterium-mediated transformation method which has been widely used in the field of sugarcane molecular breeding (Dessoky et al, 2020;Li et al, 2018). Augustine et al (2015) determined the high expression of UBI promoters compared with the CaMV 35S promoter using the Agrobacterium-mediated method in sugarcane.…”
Section: Discussionmentioning
confidence: 99%
“…In 1990, the first transgenic sugarcane was produced using the gun bombardment method (Bower & Birch, 1992). Arencibia et al (1998) later reported a novel sugarcane Agrobacterium-mediated transformation method which has been widely used in the field of sugarcane molecular breeding (Dessoky et al, 2020;Li et al, 2018). Augustine et al (2015) determined the high expression of UBI promoters compared with the CaMV 35S promoter using the Agrobacterium-mediated method in sugarcane.…”
Section: Discussionmentioning
confidence: 99%
“…A. trigonus calli explants were immersed in the Agrobacterium suspension for 5 min. Thereafter, the explants were blotted on a sterilized filter paper, placed onto a co-cultivation media (MS medium supplemented with 0.5 mg/l 2, 4-D) and were incubated under dark conditions 52 . After co-cultivation for three days, the transformed calli were transferred to MS media including 0.5 mg/l NAA, 0.5 mg/l BAP, 500 mg/l cefotaxime and 1.5 mg/l bialaphos (Sigma-Aldrich, Japan) to select the transformed calli for shoot induction 53 .…”
Section: Methodsmentioning
confidence: 99%
“…Gene gun-mediated transformation and AMT are among the most efficient and commonly utilized gene delivery methods for plant-related genetic transformation. These methods have been adopted for various crops, including soybeans (Li et al, 2017;Zhao et al, 2019;de Melo et al, 2020), sorghum (Che et al, 2018;Liu G. et al, 2019;de Melo et al, 2020;Sharma et al, 2020), maize (Char et al, 2017;Anand et al, 2018;Raji et al, 2018), sugarcane (Mayavan et al, 2015;Wu et al, 2015;Dessoky et al, 2021), wheat (Liang et al, 2018;Kumar et al, 2019;Zhang et al, 2019c), and rice (Endo et al, 2015;Ling et al, 2016;Feng et al, 2017).…”
Section: Conventional Plant Biomolecule Delivery Approaches and Their Limitationsmentioning
confidence: 99%